Another Look at a Historical Foundation of HRD: F.R. Roethlisberger’s Foreman - Julia Storberg-Walker; Laura Bierema (Adult Education Research Conference, 2006)
F.R. Roethlisberger has been recognized as the ”father” of the human relations period of management. Historically, this period was seen as a move towards more humanism in the workplace. This manuscript presents a poststructural analysis of a classic management text from this period. Findings and implications for HRD are presented.
Keywords: Human relations; Roethlisberger; F.R.; poststructural analysis